2015
DOI: 10.1038/srep11385
|View full text |Cite
|
Sign up to set email alerts
|

A G-quadruplex-binding compound showing anti-tumour activity in an in vivo model for pancreatic cancer

Abstract: We report here that a tetra-substituted naphthalene-diimide derivative (MM41) has significant in vivo anti-tumour activity against the MIA PaCa-2 pancreatic cancer xenograft model. IV administration with a twice-weekly 15 mg/kg dose produces ca 80% tumour growth decrease in a group of tumour-bearing animals. Two animals survived tumour-free after 279 days. High levels of MM41 are rapidly transported into cell nuclei and were found to accumulate in the tumour. MM41 is a quadruplex-interactive compound which bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 57 publications
3
88
0
1
Order By: Relevance
“…[13] In fact, their optoelectronic properties can be effectively tuned by substituents on the aromatic core, [14] thus giving origin to absorption and emission in the red spectroscopicw indow, which makes them appealing forf luorescence imaging and photodynamic therapy (PDT). [20] More recently,w eh ave published as eries of the NDIs 1-4 (Scheme1)h aving excellentw ater solubility and cellular entry,m erged with promising features for theranostic applications. We and others have shown that tri-and tetra-substituted as well as core-extended NDIs are potent and reversible ligands [14c, 17] and alkylating agentst argeting G-rich nucleic acids (NAs) folded into G4s.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In fact, their optoelectronic properties can be effectively tuned by substituents on the aromatic core, [14] thus giving origin to absorption and emission in the red spectroscopicw indow, which makes them appealing forf luorescence imaging and photodynamic therapy (PDT). [20] More recently,w eh ave published as eries of the NDIs 1-4 (Scheme1)h aving excellentw ater solubility and cellular entry,m erged with promising features for theranostic applications. We and others have shown that tri-and tetra-substituted as well as core-extended NDIs are potent and reversible ligands [14c, 17] and alkylating agentst argeting G-rich nucleic acids (NAs) folded into G4s.…”
Section: Introductionmentioning
confidence: 99%
“…76,81 A good example is the MD simulation used to study the interactions of tetra-substituted naphthalene diimide compound MM41 and quadruplexes formed in the gene promoter sequences, employing parmbsc0 force field supplemented with χ OL4 modifications. 36 The results from the MD simulations were able to demonstrate the favourable binding mode of MM41 to the BCL-2 quadruplexes. The interactions that MM41 made were analogous to that made by the ligand with human telomeric quadruplex.…”
Section: Automated Molecular Dockingmentioning
confidence: 90%
“…In this regard, it should be taken into account that i) cell factors (e.g., specific G4 interacting proteins) or cell conditions (e.g., chromatin status or transcriptional activity) may impinge on the ligand/G4 interaction, even in a cell-type dependent manner; ii) G4 structures with similar topologies can be amenable of stabilization by the same ligand and that iii) the vast majority of ligands reported thus far to interact with promoter G4s were primarily conceived as telomeric G4 ligands (e.g., telomestatin and RHPS4) [13, 15]. Nonetheless, pieces of evidence indicate that the “promiscuous” nature (i.e., the capability to interacts with multiple G4 targets) of some G4 ligands [11, 13, 31, 34, 35] may be of therapeutic value, as it has been recently shown for an NDI derivative able to simultaneously target the G4 within BCL2 and KRAS gene promoters in an in vivo model of pancreatic cancer [35]. …”
Section: Discussionmentioning
confidence: 99%